The History and Character Entities of Gotong Royong in the Bajo Tribe Community - Sanur, Ilham Samudra; Ahmadin, Ahmadin; Rifal, Rifal; Malihu, La; Haryono, Indriani; Ridhoh, M Yunasri (JED (Jurnal Etika Demokrasi), 2024)
The most concerning social problem today is anomalous behavior and the erosion of collective collegial values. Therefore, character development, especially related to collective values such as mutual cooperation, has become an important issue in Indonesia. This research aims to provide a comprehensive description of the history and character entities that are characteristic of the Bajo Tribe community in Wanci Island, Wakatobi Regency. This study employs a qualitative approach with a descriptive method to obtain objective data through three data collection techniques: interviews, observations, and documentation. The results of this research indicate that the migration of the Bajo tribe to the Mola region on Wanci Island began in the 1960s as a means of avoiding social conflict and accusations of involvement with the DI/TII rebellion movement on Kaledupa Island. The character of mutual cooperation upheld by the Bajo Mola community reflects a fair and inclusive social system, where the practice of mutual aid is manifested regardless of social status, age, or individual background. The conclusion of this study emphasizes the need to maintain mutual cooperation as a pillar of solidarity and social harmony in order to embody virtuous people.